Improvement of Midle Voltage Network Protection System at Kualanamu International Airport - Suwarno Suwarno; Rohana Rohana; Darwin Darwin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The electricity grid protection system at Kualanamu International Airport is urgently needed. The purpose of protection in addition to maintaining the reliability and stability of the electric power system also functions to detect disturbances, prevent damage to equipment (equipment & networks), protect humans and minimize outages in the event of a system disturbance. flight safety operations, services to passengers, operations, and equipment work at Kualanamu Airport. Safety or protection settings are based on the characteristics of the protection installed in the distribution system, which greatly affects working time, from the protection security area if there is a failure in the main protection. determine the setting of the overcurrent relay against overcurrent disturbances that may occur due to short circuit faults. To simplify the calculation of the disturbance analysis, it is simulated using the Electric Transient and Analysis Program (ETAP) Power Station12.6 software. The relay protection that is used and set is the overcurrent relay at the Kualanamu Airport Medium Voltage Network Sub Station. This relay functions to protect fault currents against ground-phase, ground-phase, ground-phase, and 3-phase. The protection relay setting refers to the provisions in force at PLN, namely for the interruption time of the 20 kV network disturbance at the substation from the time of a disturbance to the extinction of the electric arc by the opening of the power circuit breaker (PMT) the feeder is: less than or equal to 400 milliseconds and for ground-phase short circuit faults NGR12 maximum disconnection time of 500 milliseconds, NGR40 maximum disconnection time of 1000 milliseconds.